Advanced Flow Cytometry Assays for Immune Monitoring of CAR-T Cell Applications - Blache, Ulrich; Weiss, Ronald; Boldt, Andreas; Kapinsky, Michael; Blaudszun, André-René; Quaiser, Andrea; Pohl, Annabelle; Miloud, Tewfik; Burgaud, Mégane; Vucinic, Vladan; Platzbecker, Uwe; Sack, Ulrich; et al. (Frontiers in Immunology, 2021)
Adaptive immunotherapy using chimeric antigen receptor (CAR)-T cells has achieved successful remissions in refractory B-cell leukemia and B-cell lymphomas. In order to estimate both success and severe side effects of CAR-T cell therapies, longitudinal monitoring of the patient’s immune system including CAR-T cells is desirable to accompany clinical staging. To conduct research on the fate and immunological impact of infused CAR-T cells, we established standardized 13-colour/15-parameter flow cytometry assays that are suitable to characterize immune cell subpopulations in the peripheral blood during CAR-T cell treatment. The respective staining technology is based on pre-formulated dry antibody panels in a uniform format. Additionally, further antibodies of choice can be added to address specific clinical or research questions. We designed panels for the anti-CD19 CAR-T therapy and, as a proof of concept, we assessed both a healthy individual and a B-cell lymphoma patient treated with anti-CD19 CAR-T cells. We analyzed the presence of anti-CD19 CAR-T cells as well as residual CD19+ B cells, the activation status of the T-cell compartment, the expression of co-stimulatory signaling molecules and cytotoxic agents such as perforin and granzyme B. In summary, this work introduces standardized and modular flow cytometry assays for CAR-T cell clinical research, which could also be adapted in the future as quality controls during the CAR-T cell manufacturing process.